Is hypoalbuminemia a predictor marker of mortality? - Siti Maemun; Nina Mariana; Surya Otto Wijaya; Dina Oktavia; Vivi Lisdawati; Rita Rogayah (Health Science Journal of Indonesia, 2020)
Latar belakang : Hipoalbuminemia pada pasien rawat inap berkaitan dengan prognosis buruk pasien. Penelitian ini, mengidentifikasi bahwa hipoalbuminemia berat pada awal pasien masuk rawat inap sebagai prediktor andalan penanda laboratorium dalam mortalitas. Metode : Sebuah studi cross sectional pada pasien dewasa dengan hipoalbuminemia (kadar albumin < 3,5 g / dL) pada pasien rawat inap (usia > 18 tahun) pada periode Januari 2013 - Maret 2018. Kami mengevaluasi penanda prediktor kematian. Multivariat dengan regresi logistik diterapkan dalam penelitian ini. Hasil : Dari 747 hipoalbuminemia pada pasien rawat inap dengan rata-rata kadar albumin pada awal adalah 2,0 ± 0,6 g / dL. Sebagian besar pasien (83,4%) memiliki kadar albumin ≤ 2,5 g / dL (hipoalbuminemia berat), 16,6 persen memiliki > 2,5 g / dL (hipoalbuminemia ringan-sedang). Kondisi yang mendasari pasien adalah infeksi HIV / AIDS (26,9%) dan sepsis (26,6%). Proporsi multiple komorbiditas pada kelompok hipoalbuminemia berat adalah 55,1 persen Pada kelompok hipoalbuminemia berat terutama untuk kadar albumin 2,01 - 2,5 g / dL, angka mortalitas adalah 28,3 persen. Berdasarkan model regresi logistik akhir, faktor risiko kematian meliputi kadar albumin pada awal dan lama rawat pasien. Mortalitas lebih tinggi pada pasien dengan hipoalbuminemia berat (rasio odds yang disesuaikan 2,91, 95% CI 1,88-4,50) dibandingkan pasien dengan hipoalbuminemia ringan-sedang. Kesimpulan: Hipoalbuminemia berat pada awal pasien rawat inap sebagai prediktor penanda kematian di rumah sakit. Kata kunci: hipoalbuminemia, pasien rawat inap, mortalitas Abstract Background: Hypoalbuminemia in hospitalized patients has been associated with poor prognosis. In this study, we attempted to identify that severe hypoalbuminemia at baseline in hospitalized patients is a reliable predictor of laboratory marker for mortality. Methods: A cross sectional study on adults of hypoalbuminemia (albumin level < 3.5 g/dL) in hospitalized patients (aged > 18 years old) in period January 2013 - March 2018. We evaluated the predictor marker of mortality. Multivariate with the logistic regression was applied in this study. Results: Of the 747 hypoalbuminemia in hospitalized patients with the mean albumin level at baseline was 2.0 ± 0.6 g/dL. Most patients (83.4 %) had less than or equal to 2.5 g/dL albumin level (severe hypoalbuminemia), 16.6 percent had over 2.5 g/dL (mild-moderate hypoalbuminemia). The underlying condition of patients was HIV/AIDS infection (26.9%) and sepsis (26.6 %). The proportion of multiple comorbidities in the severe hypoalbuminemia group was 55.1percent. In the severe hypoalbuminemia group especially for 2.01 – 2.5 g/dL albumin level, the mortality rate was 28.3 percent. Based on the final logistic regression model, known risk factors of mortality include albumin level at baseline and length of stay. Mortality was higher among patients with severe hypoalbuminemia (adjusted odds ratio 2.91, 95 % CI 1.88-4.50) than patients with mild-moderate hypoalbuminemia. Conclusion: Severe hypoalbuminemia at baseline in the hospitalized patients was a predictor laboratorymarker of hospital mortality. Keywords: hypoalbuminemia, hospitalized patients, mortality